Progress, Freedom, and Culture of Living in Calabria - Concetta Fallanca (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
Today, discovering a new cultural interest in dwelling landscape is one of the most demanding and engaging challenges for Calabria. Focusing on a project to confer dignity, substance, and statute to those landscapes, whose essence has been depreciated for a long time, becomes fundamental. Indeed, a landscape today is still the most evident expression of the cultural model characterizing a region, given that it has always been an anticipatory factor whose features hinted at forecasting certain events before sociology understood them. To configure new perspectives for the future of our landscapes, it is necessary to improve the capacity, at an individual and public level, of taking care of our territory, taking into account above all the environmental aspects of dwelling, the physical integrity of the landscape, and the safety of urban areas. The aim pursued is the adoption of far-reaching strategies envisaging a progressive improvement that involves local scenarios and communities through investments that depend on the objectives achieved, to be verified periodically. The university and professional sectors are asked to set up new relationships so that the projects designed can impact urban planning on both a small and a large scale, consistently with the most sensible concept of sustainable development and urban and regional ecological networks, without emphasis but with determination.